Positive discipline to build student character in learning during the pandemic - Arianto, Teguh Dwi; Mulyono, Rahmat (Gema Wiralodra, 2023)
The problem in distance learning in Geography subjects at SMA Negeri 1 Rongkop is the lack of student discipline in responding to and completing assignments given by the teacher. Based on observations made during the first three months of the odd semester 2021/2022, the average student attendance rate in distance learning was 77%. Meanwhile, students have an average of 72% discipline in submitting assignments or responding to teachers. This is possible because teachers have not instilled positive discipline in students, so the results are less than optimal. The aim of this research is to describe the general picture of the application of positive discipline in the classroom, including the preparation of class agreements, implementation, and results. The research results show that the application of positive discipline through class agreements has a positive impact on teachers and students. The level of student discipline in completing assignments is 88%, and the average attendance rate is 90% with very good qualifications. The results of interviews with students conducted via Google Forms and distributed by teachers regarding the use of positive discipline received a very positive response, with 97% giving a positive response. As a result, teachers must use positive discipline during distance learning. This shows that even though learning is distance learning, critical assessment of learning can still be carried out. Average attendance is 90% with excellent qualifications. The results of interviews with students conducted via Google Forms and distributed by teachers regarding the use of positive discipline received a very positive response, with 97% giving a positive response. As a result, teachers must use positive discipline during distance learning. This shows that even though learning is distance learning, critical assessment of learning can still be carried out. Average attendance is 90% with excellent qualifications. The results of interviews with students conducted via Google Forms and distributed by teachers regarding the use of positive discipline received a very positive response, with 97% giving a positive response. As a result, teachers must use positive discipline during distance learning. This shows even though learning is distance learning, critical assessment of learning can still be carried out.